2010
DOI: 10.1001/archpediatrics.2010.100
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Prevalence, Treatment, and Outcomes of Asthma Among a Diverse Population of Children With Equal Access to Care

Abstract: To assess racial and ethnic differences in asthma prevalence, treatment patterns, and outcomes among a diverse population of children with equal access to health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 26 publications
0
50
0
Order By: Relevance
“…These findings are consistent with findings among children outside of foster care. Previous research has found that non-Hispanic black children are less likely to use controller medication than non-Hispanic white children (McDaniel & Waldfogel, 2012;Sarpong & Miller, 2013) and have more avoidable asthma hospitalizations and asthma-related emergency department visits (Stewart et al, 2010). However, these studies focused on children raised by parents in their homes, not in foster care by foster parents or shift personnel in congregate care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with findings among children outside of foster care. Previous research has found that non-Hispanic black children are less likely to use controller medication than non-Hispanic white children (McDaniel & Waldfogel, 2012;Sarpong & Miller, 2013) and have more avoidable asthma hospitalizations and asthma-related emergency department visits (Stewart et al, 2010). However, these studies focused on children raised by parents in their homes, not in foster care by foster parents or shift personnel in congregate care.…”
Section: Discussionmentioning
confidence: 99%
“…The study sample was drawn from the population of Illinois children aged 5-17 years eligible for Medicaid due to child welfare system involvement or income between fiscal year (FY) 2010(July 1, 2009-June 30, 2012. We excluded children eligible for Medicaid due to disability although some of the children in foster care may have qualifying disabilities.…”
Section: Data and Study Samplementioning
confidence: 99%
“…A retrospective cohort analysis by Stewart et al, 43 in the military health system, assessed racial and ethnic differences in asthma prevalence, treatment patterns, and outcomes among a diverse population of children with equal access to healthcare. The theory behind the study was that the military health system provides comprehensive health insurance to a racially and ethnically diverse population, so studying disparities in healthcare treatment and outcomes in that population could substantially improve our understanding of possible effects of universal coverage on reducing disparities in healthcare.…”
Section: Sociocultural Factorsmentioning
confidence: 99%
“…1,2 Asthma is the most common chronic physical health condition of childhood, and morbidity disproportionately affects racial minorities. [3][4][5][6][7][8][9][10] Population-based studies that report racial disparities, however, rarely include patient-level details beyond traditional sociodemographic factors. 9 Further characterization of the challenges families face may help identify risks amenable to both clinical and public health interventions that could prevent subsequent morbidity and reduce disparities.…”
mentioning
confidence: 99%